PENGUATAN PERAN GURU DALAM GREEN EDUCATION MOVEMENT UNTUK MEWUJUDKAN ECO YOUTH DI ERA DIGITAL - Dian Samitra; Zico Fakhrur Rozi (LPPM Institut Pendidikan Nusantara Global, 2026)
This activity aims to strengthen the role of teachers in supporting the Green Education Movement as an effort to foster environmental awareness and care-oriented character among the younger generation. The issue addressed relates to the low integration of sustainability values in the learning process and the need to enhance teachers’ capacity as drivers of ecologically conscious education. The activity was carried out through the delivery of materials and experience-sharing sessions for teachers in the regions of Lubuklinggau City, Musi Rawas, and Musi Rawas Utara on April 24, 2025, at the Embun Semimbar Hall of PGRI Silampari University. The approach used included strengthening the role of teachers as role models, facilitators, and designers of environmentally based learning by utilizing digital technology. The results of the activity showed an increase in teachers’ understanding and commitment to integrating environmental issues into learning, as well as encouraging students to actively participate in eco-friendly activities. This activity leads toward the implementation of sustainable education that is relevant to the needs of the digital era and has the potential to produce eco-youth generations with global awareness and a strong sense of responsibility for environmental preservation.